Analisis Dampak Pembelajaran Nilai Dasar Perdamaian dalam Pembentukan Sikap Hidup Damai: Analysis of the Impact of Learning Basic Peace Values in Forming a Peaceful Life Attitude - Subekan, Achmat; Azwar, Azwar (Litera Academica Publishing, 2024)
This study aims to find out the participants' responses to the material on the Basic Values of Peace and to find out changes in the attitude of the participants resulting from the material on the Basic Values of Peace in the activities of the Ministry of Finance of One Country. This research was conducted with quantitative methods. Data collection was carried out using a questionnaire which was distributed to all participants via the Google form. The research was conducted on junior high school students who were participants in the One Country Ministry of Finance activities. The results showed that: first, the participants really felt the need to get material on the basic values of peace even though some of them claimed to have implemented these basic values. They also feel the great benefits of learning materials in forming a peaceful attitude in life; second, a positive change in attitude occurs as a result of learning the basic value of peace. They are more able to accept their physical condition, are better able to respond to differences, and are more motivated to create harmonious relationships with others.